Two-Intervals Hardening Function in a Phase-Field Damage Model for the Simulation of Aluminum Alloy Ductile Behavior - Vladimir Dunić (MDPI AG, 2021)
The aluminum alloys (AA) are among the most utilized materials in engineering structures, which induces the need for careful investigation, testing, and possibilities for accurate simulation of the structure’s response. AA 5083-H111 specimens were used to investigate the possibility of employing a Phase-Field Damage Model (PFDM) for the simulation of AA structures’ behavior. The specimens were mechanically tested by uniaxial tensile loading tests. Based on the obtained results, the PFDM was employed with a von Mises plasticity model, implemented in the Finite Element Method software. The plasticity model was extended by modification of the hardening function defined in two-intervals: a linear hardening and a Simo-type hardening. An excellent superposition of the simulation and experimental force-displacement response was recorded. These findings suggest that the AA structures’ response can be successfully simulated in the elastic-plastic domain, as well as its failure by damage being controlled.